Clinical features and outcome of Corona Virus Disease – 19 infection among pregnant Jordanian women - Qudsieh , Suhair; Abu Mahfouz , Ismaiel; Abu Assaf, Gharam (Jordan Medical Journal, 2022)
Background: Studies among pregnant women who had COVID-19 are limited. Earlier reports had shown that COVID-19 during pregnancy is associated with increased risks of spontaneous miscarriage, intrauterine growth restriction and preterm delivery. More evidence is needed as most published studies involved small numbers. This study aimed to review the clinical features and outcomes of COVID-19 positive pregnant women in Jordan. Methods: A retrospective review of medical records of 112 COVID-19 positive pregnant women in Jordan during the period of March to October 2020. The data collected included maternal age, comorbidities, gestational age, presenting symptoms, laboratory results, maternal and neonatal outcomes. Results: The mean (±SD) for age and gestational age were 30 (±5.4) years and 32(±8.9) weeks, respectively. Additionally, 88 women (79%)were in the third trimester, and 79 women (70.5%) were multiparous. Data analysis showed that 62 women (55.4%) were symptomatic, and the most common symptoms were cough and dyspnea in 66% and 47%, respectively. The most common obstetric complications were preterm delivery (19%) and anemia (18%). 68% were delivered by cesarean section and 4.5% died. Conclusion: Most pregnant women in this study were symptomatic with cough being the most common symptom, and the majority were diagnosed in the third trimester, this suggests that advanced gestational age may be a risk factor for catching the infection and being symptomatic. Therefore, pregnant women and healthcare practitioners should consider the impact of gestational age on the disease behavior, and the rate of preterm labor and maternal death.